Analysis of "Harmony" and "Unity" Concepts in Indonesian and Chinese Culture - Yu LU (Mandarinable: Journal of Chinese Studies, 2022)
"Harmony" and "Unity" are important concepts in ancient Chinese philosophy and the basic spirits of traditional Chinese culture, which advocate seeking a harmonious coexistence based on differences. The ideas of harmony and seeking common ground while reserving differences can also be found in Indonesia's traditional culture and its modern concept of building a state, which is naturally similar to the Chinese concepts of "Harmony" and "Unity". In the context of contemporary social development, which is increasingly globalized, diversified, and complicated, the communication and understanding of the common ideology of the two countries is conducive to the mutual absorption and integration of different cultures, and also to the construction of a community with a shared future based on mutual tolerance, interdependence and joint development.